Mesomorphic and structural properties of liquid crystalline side-chain polymethacrylates: from smectic C* to columnar phases. Issue 6 (3rd May 2019) - Sulyanov, Sergey N.; Dorovatovskii, Pavel V.; Bobrovsky, Alexey Yu.; Shibaev, Valery P.; Cigl, Martin; Hamplová, Vĕra; Bubnov, Alexej; Ostrovskii, Boris I.
ABSTRACT: The chiral methacrylate monomers with photosensitive azobenzene group possessing the orthogonal smectic A* and tilted smectic C* (Sm-C*) phases have been synthesised and characterised. The monomers have been used as functional side chains for the design of corresponding polymethacrylates. X-ray diffraction has been applied to elucidate the structure and phase behaviour of liquid-crystalline side-chain polymethacrylates with azobenzene-containing central core, chiral fragments and aliphatic spacers and tails of different length. X-ray patterns of polymethacrylates oriented fibres impose the tilted Sm-C* order as a basic structure of these materials. This is complemented by a regular pattern of small-angle diffuse spots, which implies complex positional order on the local scale and serves as a precursor for the formation of a columnar phase. The increase of the total length of the aliphatic tail and spacer of the side-chain fragments leads to formation of the tilted columnar phase (Coltilt *) with two-dimensional monoclinic lattice. For the polymer containing 10 methylene units in both, spacer and aliphatic tail, the Coltilt * precedes the formation of the Sm-C* phase. The observed structural changes are explained as due to coupling between the smectic ordering of the mesogenic side groups and the polymer backbone conformation. Graphical Abstract: